Hearing God's Voice My Life with Scripture in the Churches of Christ - Olbricht, Thomas H. (Abilene Christian University Press, 1996)
In times of change, Christians have always sought enduring answers from the pages of Scripture. Our hermeneutic-our method of organizing and understanding the message of the Bible-predetermines what answers we will glean. But is our process of understanding based on the Bible, or on our cultural and historical assumptions? In this autobiography, Thomas H. Olbricht (1929-2020) looks back on the last sixty years in Churches of Christ and offers his observations of how our perceptions of Scripture have changed and evolved. He clears a path through the shifting thickets of an unsteady world; a path that leads toward the Everlasting-a way to hear God's voice.